Pengaruh Halal Brand Awareness Terhadap Purchase Intention Dengan Attitude Sebagai Mediasi Pada Produk Skincare Safi Di Kota Padang - Sari Ayu, Fanita; Yolanda, Mike (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The increasing awareness of Muslim consumers regarding the importance of halal products has encouraged the emergence of various halal cosmetic brands, one of which is Safi. However, despite obtaining halal certification from JAKIM and MUI, Safi products have experienced a decline in sales in Indonesia in the past five years. This study aims to analyze the effect of halal brand awareness on purchase intention, with attitude as a mediating variable, among Safi product users in Padang City. This study used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that halal brand awareness has a positive and significant effect on purchase intention, both directly and indirectly through mediating attitude. This finding underscores the importance of forming positive consumer attitudes towards halal brands in increasing purchase intention. The practical implications of this study encourage halal cosmetic companies to understand brand awareness integrated with the values ​​and attitudes of Muslim consumers. Keywords: Halal Brand Awareness, Attitude, Purchase Intention, Halal Cosmetics, Safi.